Pengaruh Komunikasi Internal, Lingkungan Kerja, Dan Motivasi Terhadap Kepuasan Kerja Pegawai Pemerintahan Desa Sukopuro Kecamatan Jabung Kabupaten Malang - Rahmadhani, Inneke Putri; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of internal communication, work environment, and motivation on job satisfaction among government employees of Sukopuro Village, Jabung District, Malang Regency. This study employs a quantitative method with a survey approach. Data was collected through questionnaires distributed to all 83 village government employees in Sukopuro using a saturated sampling technique. Data analysis was conducted using multiple linear regression to determine the impact of independent variables on the dependent variable. The findings indicate that internal communication, work environment, and motivation have a positive and significant impact on job satisfaction among village government employees. These findings affirm that effective human resource management in village government significantly depends on these factors to improve employee well-being and provide better public services.  Keywords : Internal Communication, Work Environment, Motivation, Job Satisfaction, Village Government Employees.